Seasoned equity offerings: determining the characteristics of Malaysian firms in consumers product industries / Amirul Aiman A Rashid - A Rashid, Amirul Aiman (2017)
Seasoned equity offerings (SEOs) are sales of stock after the initial public offering. It was to raise funds from the sale of stock rather issuing additional debt. I, the author, adopt a method that been had used to predict the characteristic of firms that likely to undertake the form of financing through SEO. The technique was based on logistic regression where by the firm specific variables are acquired from the perspective of the firm's returned earning, cash-flow investment, net income, capital expenditure and long-term debt. A software package called SPSS (Statistical Package for the Social Sciences) is being used in finding and analyzing the data. In order to observe the relationship between the Dependent variable, likelihood of firm choosing SEO, and the independent variables, returned earning, cash-flow investment, net income, capital expenditure and long-term debt, wald test produced by SPSS are used for analysis during this research.